Development of a subunit vaccine containing recombinant Riemerella anatipestifer outer membrane protein A and CpG ODN adjuvant. Issue 1 (1st January 2015) - Chu, Chun-Yen; Liu, Chia-Hui; Liou, Jhong-Jie; Lee, Jai-Wei; Cheng, Li-Ting
Highlights OmpA was combined with CpG ODN plasmids as a vaccine against R. anatipestifer. CpG ODN enhanced IFN-γ, IL-12 and IL-6 production by duck PBMC. CpG ODN helped increase antigen-specific lymphocyte population and T cell activation. OmpA + CpG ODN reduced pathological lesions by 90% in a challenge experiment.